Why International Organizations Don't Learn: Dissent Suppression as a Source of IO Dysfunction. - Christian, Ben (International Studies Quarterly, 2025)
International organizations (IOs) need to learn from their mistakes in order to improve their performance. Over the past decades, IOs have therefore invested significantly in building a professional learning infrastructure. However, as recent studies show, many IOs still struggle to learn from their mistakes. Why do IOs not learn despite all these formal learning processes and tools? I argue that the internal "criticism culture"—the way IOs deal with criticism from their own employees—is an overlooked but crucial variable that can help us explain the lack of learning in IOs. To illustrate this argument, I draw on an in-depth case study of the UN Secretariat and more than 50 interviews with UN staff members. First, I show that the internal criticism culture in the UN Secretariat's Peace and Security Pillar is repressive and self-restrained. Second, I demonstrate that this criticism culture leads to a double blockade that prevents the organization's formal learning infrastructure from performing as intended: UN employees do not dare to voice criticism in official formats, and "learning products" are glossed over as they move up the ranks. As a consequence, the IO lacks a necessary stimulus for learning, which results in performance problems.